Foliar transcriptomes reveal candidate genes for late blight resistance in cultivars of diploid potato Solanum tuberosum L. Andigenum Group - Cruz, G. de la; Blas, R.; Pérez, W.; Neyra, E.; Ortíz, R. (Frontiers Media, 2023)
Characterization of major resistance (R) genes to late blight (LB) –caused by the oomycete Phytophthora infestans– is very important for potato breeding. The objective of this study was to identify novel genes for resistance to LB from diploid Solanum tuberosum L. Andigenum Group (StAG) cultivar accessions. Using comparative analysis with a edgeR bioconductor package for differential expression analysis of transcriptomes, two of these accessions with contrasting levels of resistance to LB were analyzed using digital gene expression data. As a result, various differentially expressed genes (P ≤ 0.0001, Log2FC ≥ 2, FDR < 0.001) were noted. The combination of transcriptomic analysis provided 303 candidate genes that are overexpressed and underexpressed, thereby giving high resistance to LB. The functional analysis showed differential expression of R genes and their corresponding proteins related to disease resistance, NBS-LRR domain proteins, and specific disease resistance proteins. Comparative analysis of specific tissue transcriptomes in resistant and susceptible genotypes can be used for rapidly identifying candidate R genes, thus adding novel genes from diploid StAG cultivar accessions for host plant resistance to P. infestans in potato.